The Impact of Support and Reduction Temperature on the Catalytic Activity of Bimetallic Nickel-Zirconium Catalysts in the Hydrocracking Reaction of Algal Oil from Spirulina Platensis - Lukasz Szkudlarek; Karolina A. Chalupka-Spiewak; Aleksandra Zimon; Michal Binczarski; Waldemar Maniukiewicz; Pawel Mierczynski; Malgorzata Iwona Szynkowska-Jozwik (Molecules)
The aim of this work was to investigate the hydrocracking of algae oil derived from Spirulina Platensis species catalyzed with bi-component nickel-zirconia catalysts supported onto different carriers (BEA, ZSM-5 and Al2O3) in an autoclave at 320 °C for 2 h with a hydrogen pressure of 75 bar. All catalysts were prepared using the wet co-impregnation method and were characterized by H2-TPR, XRD, NH3-TPD, BET and SEM-EDS. Before reactions, catalysts were calcined at 600 °C for 4 h in a muffle furnace, then reduced with 5%H2-95%Ar reducing mixture at 500 °C, 600 °C or 700 °C for 2 h. The obtained products were analyzed and identified by HPLC and GC-MS techniques. In addition to the investigation of the support effect, the influence of the reduction temperature of catalytic systems on the catalytic activity and selectivity of the products was also examined. The activity results show that Ni-Zr systems supported on zeolites exhibited high conversion of algal oil. A gradual decrease in conversion was observed when increasing the reduction temperature of the catalyst (from 500 °C to 600 °C and 700 °C) for BEA zeolite catalysts. The reaction products contain hydrocarbons from C7 to C33 (for zeolite-supported catalysts) and C36 (for systems on Al2O3). The identified hydrocarbons mainly belong to the gasoil fraction (C14–C22). In the research, the best catalyst for the algal oil hydrocracking reaction was found to be the 5%Ni-5%Zr/BEA system reduced at 600 °C, which exhibited the second highest algal oil conversion (94.0%). The differences in catalytic activity that occur are due to the differences in the specific surface area among the supports and to differences in the acidity of the catalyst surface depending on the reduction temperature.